2022
DOI: 10.3390/cancers14051210
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Post-Resection Urine Metabolic Profiles of Bladder Cancer Patients: Results of Preliminary Studies on Time Series Metabolomics Analysis

Abstract: The incidence of bladder cancer (BCa) has remained high for many years. Nevertheless, its pathomechanism has not yet been fully understood and is still being studied. Therefore, multiplatform untargeted urinary metabolomics analysis has been performed in order to study differences in the metabolic profiles of urine samples collected at three time points: before transurethral resection of bladder tumor (TURBT), the day after the procedure and two weeks after TURBT. Collected samples were analyzed with the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…After reviewing the titles, abstracts, and the full texts, we selected 30 studies for qualitative synthesis ( Fig. 1 ) [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ].
Figure 1 Flowchart of selected studies.
…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the titles, abstracts, and the full texts, we selected 30 studies for qualitative synthesis ( Fig. 1 ) [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ].
Figure 1 Flowchart of selected studies.
…”
Section: Resultsmentioning
confidence: 99%
“…Bca is still a worldwide problem in people over the age of 50, and the incidence differs among races, with a lower morbidity but a poor survival rate in African Americans (1). The mortality rates for men and women are similar, and the development risk is four times higher in men than in women (2). The risk factors for Bca include age, race, sex, body mass index (BMI), smoking, pathogen infections, and socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%
“…Sphingomyelin and lysophosphatidylethanolamine were identified as putative biomarkers in the time series analysis for discriminating between multiple sclerosis patients and healthy individuals [13]. Jacyna, et al [14] investigated the urine metabolic profiles of bladder cancer patients pre-and post-resection. It was reported that hippuric acid, pentanedioic acid and uridine could potentially be used for sample differentiation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Jacyna, et al [14] investigated the urine metabolic profiles of bladder cancer patients pre-and post-resection. It was reported that hippuric acid, pentanedioic acid and uridine could potentially be used for sample differentiation [14]. Huang, et al [15] analyzed the time-series lipidomics data to study the development of hepatocellular carcinoma in a hepatocarcinogenesis rat model.…”
Section: Introductionmentioning
confidence: 99%